PENINGKATAN PRESTASI BELAJAR MELALUI BIDANG BIMBINGAN PRIBADI DAN BIMBINGAN SOSIAL MATERI MENGATASI STRES DAN DEPRESI - Agusyan Dewit; Deka Ismi Mori Saputra (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
ABSTRACT This research is motivated by the fact that learning in the field of personal and social guidance is always low, students have difficulty understanding learning. The main aim of this research is to help students to overcome that group services can improve students' learning achievements and to find out how to provide group services so that they can increasing student learning achievement. This research uses an action research design based on a naturalistic-qualitative approach. This approach views reality as having complete plural dimensions and forming one unit. The results of this research show that group tutoring services can increase learning achievement in the field of tutoring in the topic of dealing with student stress and depression. This can be seen from the increase in student learning outcomes before and after classroom action research treatment. before the research the average student score was 59, in Cycle I after the group service the average student score was 76 and in Cycle II the average student score was 82.4. Key words: learning achievement, personal guidance, stress and depression.